Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.2307/2446229
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Quantity and Quality as Explanations for Low Seed Set in Small Populations Exemplified by Eupatorium (Asteraceae)

Abstract: As plant populations decrease in size, reduced seed set may contribute to their ultimate extirpation. In this study, effects of pollen quantity and compatibility relationships (quality) on seed set were investigated in a rare species (Eupatorium resinosum) and a closely related common species (E. perfoliatum). The impact of pollen quantity was studied through pollen supplementation experiments in two populations of each species. Addition of pollen increased seed set only in the smaller population of E. resinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 23 publications
2
78
0
Order By: Relevance
“…This has been invoked to explain the reduced fecundity in small endangered populations of self-incompatible plants (for example, Les et al 1991;Aspinwall and Christian 1992;Demauro 1993;Byers 1995). We found a quite high number of S-alleles in all populations except the smallest, Punta Calcina.…”
Section: Discussionmentioning
confidence: 54%
“…This has been invoked to explain the reduced fecundity in small endangered populations of self-incompatible plants (for example, Les et al 1991;Aspinwall and Christian 1992;Demauro 1993;Byers 1995). We found a quite high number of S-alleles in all populations except the smallest, Punta Calcina.…”
Section: Discussionmentioning
confidence: 54%
“…Lower fruit and seed set in plants of small habitat fragments have been observed for many species of tropical and temperate vegetation (e.g., Jennersten, 1988;Jennersten, & Nilsson, 1993;Aizen, & Feinsinger, 1994a;Byers, 1995;Oostermeijer, Altenburg, & den Nijs, 1995;Ågren, 1996;Cunningham, 2000;Quesada et al, 2003). Other species either do not show any different response in reproductive output between fragmented and continuous forest or present even higher reproductive output in smaller fragments and open areas than in continuous forest (e.g., Costin, Morgan, & Young, 2001;Dick, 2001;Lopes, & Buzato, 2007;Dunley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In these pseudo self compatible (PSC) species SI operates as a quantitative, rather than a qualitative, trait due to the segregation of unlinked genes that modify the strength of SI (Good-Avila & al., 2008). Whether such intermediate strategies are widespread, artefactual or evolutionary labile is under debate (see Raduski & al., 2012 and references therein the path towards self-compatibility (Allen & Hiscock, 2008) particularly favored when mates are limiting (Busch & Schoen, 2008), for instance in small populations of endemic spe cies (e.g., Byers, 1995). Recent comparative analyses suggested that endemic species tend to evolve self-compatibility (SC) systems (Alonso & al., 2010) but PSC was not considered as a possible stage.…”
Section: Introductionmentioning
confidence: 99%
“…Recent comparative analyses suggested that endemic species tend to evolve self-compatibility (SC) systems (Alonso & al., 2010) but PSC was not considered as a possible stage. Interestingly, PSC has been found in several endemic species (e.g., Byers, 1995;Bush, 2005;Glemin & al., 2005, Ortiz & al., 2006Nielsen & al., 2007;Weber & Goodwillie, 2009;Crawford & al., 2010;Narbona & al., 2011) suggesting that endemics could be good species candidates for studying ongoing evolutionary changes in mating system. Endemic species frequently experience high pollen limitation in the characteristically diverse communities where they occur (Vamosi & al., 2006;Alonso & al., 2010).…”
Section: Introductionmentioning
confidence: 99%